2015
DOI: 10.3389/fmicb.2015.01130
|View full text |Cite
|
Sign up to set email alerts
|

VarR controls colonization and virulence in the marine macroalgal pathogen Nautella italica R11

Abstract: There is increasing evidence to suggest that macroalgae (seaweeds) are susceptible to infectious disease. However, to date, little is known about the mechanisms that facilitate the colonization and virulence of microbial seaweed pathogens. One well-described example of a seaweed disease is the bleaching of the red alga Delisea pulchra, which can be caused by the bacterium Nautella italica R11, a member of the Roseobacter clade. This pathogen contains a unique luxR-type gene, varR, which we hypothesize controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 107 publications
(134 reference statements)
0
35
0
Order By: Relevance
“…N. italica R11 has been identified as a causative agent of bleaching disease in D. pulchra, yet there is a paucity of knowledge regarding the gene regulation and molecular mechanisms that mediate this host–pathogen interaction. In N. italica R11, the LuxR homolog VarR was previously shown to control phenotypes involved in biofilm formation and virulence (Gardiner, Fernandes et al., ). Further proteomic analysis demonstrated that VarR positively controls a range of proteins for surface colonization and biofilm maturation, such as signal transduction mechanisms, and genes for nutrient acquisition and metabolism (Gardiner, Fernandes et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…N. italica R11 has been identified as a causative agent of bleaching disease in D. pulchra, yet there is a paucity of knowledge regarding the gene regulation and molecular mechanisms that mediate this host–pathogen interaction. In N. italica R11, the LuxR homolog VarR was previously shown to control phenotypes involved in biofilm formation and virulence (Gardiner, Fernandes et al., ). Further proteomic analysis demonstrated that VarR positively controls a range of proteins for surface colonization and biofilm maturation, such as signal transduction mechanisms, and genes for nutrient acquisition and metabolism (Gardiner, Fernandes et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…An N. italica R11 raiR allelic replacement mutant (∆ raiR ) strain and complement (C∆ raiR ) strain were constructed using the Splicing by Overlap Extension PCR (SOE‐PCR) strategy coupled with biparental conjugation following the method of Gardiner, Fernandes et al. (). Briefly, a single homologous recombination event between the SOE‐PCR fragment and the genome of N. italica R11 generated the chloramphenicol‐resistant mutant strain, Δ raiR .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations